Platinum(II) chloride-catalyzed stereoselective domino enyne isomerization/Diels-Alder reaction - Schelwies, Mathias; Farwick, Andreas; Rominger, Frank; Helmchen, Günter (The journal of organic chemistry, 2010)
Chiral 1,6-enynes were prepared via Ir-catalyzed allylic substitutions. Their platinum(II) chloride-catalyzed domino enyne isomerization/Diels−Alder reaction provided stereoselective access to complex heterocycles. Very high diastereoselectivity was induced by a chirality center of the enyne.